Determination of liver enzyme levels in patients that infected with E.histolytica in Samarra city (Journal of Pharmaceutical Negative Results, 2022)
The current study aimed to reveal the evaluation of the level of liver function in infected with the parasite Entamoeba histolytica, Blood samples were collected during the period from the beginning of August 2021 until the month of April 2022. The separated sera were kept at -20 degrees until use. Enzyme-linked immunosorbent adsorption (ELISA) technique was used to detect dysentery amoeba infection. ALP, ALT, AST concentrations were measured using Spectophotomertric method. In the current study, 250 samples were taken, and the number of samples infected with the dysentery amoeba parasite was 120 samples with a percentage of 48%, and the infection rate for sex was 85 samples infected with males by 59%, and about 35 samples were infected with 33% of females.The results of the current study showed a significant P≤0.05 increase in the levels of (GPT 4.464±54.214), , ALP 0.5542±6.7440 when compared with control group (7.14 ± 39.340 ) and 0.5699 ± 5.8061) There was an increase in the levels of (ALT 4.409±46.35), AST 7.19±62.44, ALP 0.42386±6.4563) when compared with control group (7.14±39.340, 9.75±54.16, 0.5699±5.8061 respectively.